Research progress and applications on TiB2 ceramic - WANG Xianhe; XIE Xingcheng; YANG Jian; LIN Zhongkun; SHI Zhiguang; LIU Hao; CAO Ruijun (Fenmo yejin jishu)
With high melting point, high hardness, high thermal conductivity, excellent electrical conductivity, and high temperature oxidation resistance, the TiB2 ceramic has been applied in the fields of aerospace, machinery manufacturing, metal smelting, electronic information, and so on. However, the high-end manufacturing application of TiB2 ceramic has been limited by the low relative density and the difficulty of machine-processing. The densification of TiB2 ceramic could be improved by doping modification, adding sintering additives, optimizing sintering process, and so on, which significantly improves the mechanical properties. The research progress of high-performance TiB2 ceramic in terms of composition design and sintering processing was reviewed in this paper. The applications of TiB2 ceramic were also prospected on precision tools, bulletproof armor, and cathode tools.